PENGARUH INDEKS SAHAM STI, TAIEX, KOSPI, HANGSENG TERHADAP PERGERAKAN INDEKS SAHAM GABUNGAN PADA BEI - Sidiq, Ahmad (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2010)
Along with market development and demand to be more increase efficiency with competitiveness at regional area. Worldwide economy globalization pushes market dynamics and international finance industrial. is price index pacific asia bations stock exchange share (singapore, taiwan, korean, hongkong) influential towards movement ihsg in indonesia effect exchange? Analysis model regression multivariable is used to detect Asia Pacific price index influence towards movement IHSG partially and simultaneous. partially pacific asia bations stock exchange share price index (sti, hanseng, kospi) influential towards IHSG according to significant. index Taiex variable influential not significant towards movement IHSG. simultaneously Asia Pacific bations stock exchange share price index variable (sti, taiex, hanseng, kospi) influential towards IHSG.